Advanced noise abatement departure procedures: custom-optimised departure profiles. (May 2015) - Hebly, S. J.; Visser, H. G.
Abstract: This paper presents the concept of custom-optimised departure profiles, as an advanced form of noise abatement departure procedures. This concept relies on fixed routes in combination with individually optimised vertical departure profiles. Although the use of fixed ground tracks results in some loss in environmental performance, the high degree of complexity associated with free routing is eliminated as well, leading to a concept that does not appear to be incompatible with today's Air Traffic Control (ATC) principles. By using a primitive form of trajectory negotiation between airline and ATC, selected flights can be allowed to perform an optimised departure without interfering with non-participating traffic. Apart from the concept itself, this paper also describes the departure profile optimisation tool, which is based on a previously developed trajectory optimisation framework called NOISHHH. Finally, in a numerical example, a current standard ICAO-A procedure is compared with two optimised profiles for a Boeing 737 departure from Amsterdam Airport. Fuel burn, noise impact and the required flight time to a specified point are compared for the three departure profiles. It is shown that the custom-optimised departure profiles have the potential to both reduce fuel burn as well as noise exposure, relative to the ICAO-A procedure.